Is visual search strategy different between level of judo coach when acquiring visual information from the preparation phase of judo contests? - Robertson, P. R.; Callan, M.; Nevison, C.; Timmis, M. A. (International Journal of Sports Science & Coaching, 2018)
Judo contests are complex situations for coaches observing them. Identifying where judo coaches look (i.e. their visual search strategy) when observing contests can help identify visual information they may use to inform coaching decisions. The current exploratory study investigated the visual search strategies of elite, sub-elite, and non-judo coaches when observing the preparation phase (viewed from video footage) of elite-level judo contests. Participants' eye movements were recorded using a mobile eye-tracker. Participants were instructed to provide verbal coaching instructions to improve a specified judoka's (judo athlete) performance at set times during the footage. Elite coaches fixated significantly more frequently and longer on the specified judoka's upper body (p < 0.05) compared to the opponent's upper body and other key areas within the display. Sub-elite and non-judo coaches demonstrated no significant difference in the frequency or overall length of fixation between the judokas' upper bodies. The visual search strategy of elite judo coaches may have been a purposeful attempt to obtain accurate information about the judoka's attacking intentions early within the contest. This visual search strategy can be attributed to elite judokas' attempting to disguise their attacking intentions. Furthermore, elite coaches may have used the specified judoka's upper body as a visual pivot.